A house for Hermit Crab - Carle, Eric. (New York : Simon & Schuster Books for Young Readers, 2009)
A hermit crab who has outgrown his old shell moves into a new one, which he decorates and enhances with the sea creatures he meets in his travels.
Originally published: Saxonville, Mass. : Picture Book Studio, c1987.
Keywords: Hermit crabs -- Fiction; Crabs -- Fiction; Marine animals -- Fiction; Dwellings -- Fiction; Houses -- Fiction